Explaining the relationship between job insecurity and creativity: A test of cognitive and affective mediators. Issue 3 (30th September 2019) - Probst, Tahira; Chizh, Alina; Hu, Sanman; Jiang, Lixin; Austin, Christopher
Abstract : Purpose: Despite a large body of literature on the negative consequences of job insecurity, one outcome – job creativity – has received relatively scant attention. While initial studies established a relationship between job insecurity and creativity, the explanatory mechanisms for this relationship have yet to be fully explored. The paper aims to discuss this issue. Design/methodology/approach: Using threat-rigidity theory and broaden-and-build theory as a conceptual foundation, the authors implemented a two-country temporally lagged research design (the USA ( n = 390); China ( n = 346)) to test two potential mediating mechanisms – cognitive failures and positive job-related affect – as explanatory variables between quantitative and qualitative forms of job insecurity and self- and other-rated measures of creative performance. Findings: Results from both countries suggest that job-related affective well-being and employee cognitive failures both explained the relationship between job insecurity and creative performance. However, affective well-being was a better explanatory variable for the relation between job insecurity and self-rated creative performance, whereas cognitive failures better accounted for the relationship between job insecurity and performance on an idea generation task. Research limitations/implications: The authors discuss the implications of these findings from measurement, theoretical and practical perspectives. Originality/value: The authors extend prior research on the relationship between job insecurity and creativity by: considering both quantitative and qualitative job insecurity, examining their relationships with both self- and other-rated assessments of creative job performance, and testing cognitive and affective mediating mechanisms explaining these relationships.